The Effect of Brand Image and Brand Trust on Purchase Decisions with eWOM as a Moderating Variable - Nailah Early Azzahra; Asep Supriadi; Hayati Nupus (LPPM Politeknik Pratama, 2026)
This study aims to examine the influence of brand image and brand trust on purchase decisions, with electronic word of mouth (eWOM) serving as a moderating variable. The research employs a quantitative methodology with a descriptive approach. Data were collected through questionnaires and literature review. The population comprised Samsung smartphone users in Tangerang Regency, and a purposive sampling technique was applied to obtain a sample of 119 respondents. Structural Equation Modeling (SEM) was utilized for data analysis, employing the SmartPLS 4 software. The results indicate the following: (1) Brand image exerts a positive and significant influence on purchase decisions. (2) Brand trust exerts a positive and significant influence on purchase decisions. (3) eWOM has a positive and significant effect on purchase decisions. (4) eWOM was not found to moderate the relationship between brand image and brand trust on purchase decisions, either by strengthening or weakening that effect.